IMPACT LIMITATION OF SOCIAL SCALE WITH THE MOVEMENT SOCIAL AND PHYSICAL DISTANCING OF ANXIETY SOCIETY FOR PANDEMIC DISEASE CORONAVIRUS 2019 (COVID-19) IN PEKALANGAN CIREBON - Rully - Annisa; Mohamad Jihad Faturrachman (Jurnal Ilmu Kesehatan, 2021)
Background: Pandemic outbreak is a time of global emergency. Large-scale social restrictions during a pandemic are a contributing factor to psychiatric comorbidities. One of the psychological problems that arise during this pandemic is anxiety. Objective: To analyze the impact of Large-Scale Social Restrictions with social and physical distancing movements on public anxiety during the pandemic outbreak Coronavirus Disease 2019 (COVID-19). Methods: This study is a qualitative research approach using a phenomenological study. Participants / informants were taken purposively. The analysis technique used is data triangulation. Results: The results showed five main themes: (1) Community description (2) Public perception (3) Community feeling (4) Community action (5) Change in people's physical health. Conclusion: During the Covid-19 pandemic outbreak, participants experienced mild to severe anxiety, which was largely influenced by almost all aspects, but the most prominent aspect was the economy, which was the source of increased stressors and changes in the coping response of the community.